Pengaruh Media Buku Saku Digital Terhadap Pengetahuan Ibu Tentang Pencegahan ISPA Pada Balita (Jurnal Kesehatan Siliwangi, 2023)
UNICEF data informs that every year more than 2 million children under five die from Acute Respiratory Infections (ARI). The high rate of ARI in children under five, one of which is caused by the mother's lack of knowledge. The results of Riskesdas 2018 state that the prevalence of ARI in Indonesia is mostly in the one to four year age group. One of the regencies in West Java Province with high cases is Tasikmalaya, amounting to 3,073. The incidence of ARI at the Sukahening Health Center was 974 cases. One of the efforts that can be done to reduce the incidence of ARI is to increase maternal knowledge by providing health education through digital pocket books. The purpose of this research is to analyzed the effect of digital pocket book media on mother's knowledge about ARI prevention in toddlers in Sukahening Village. Method This study uses a quasi-experimental design with a one group pre-test post-test design. The number of samples as many as 38 mothers was obtained by using cluster random sampling technique. The instrument used to measure knowledge, namely questionnaires and data analysis using the wilcoxon test, obtained = 0.000 so it can be concluded that digital pocket book media has an effect on mothers' knowledge of ARI prevention in toddlers. This digital pocket book media can be used as a medium to educate mothers about the prevention of ARI in toddlers.